The Fear of Artificial Intelligence and Climate Change : Presentation of future in the Horizon Zero Dawn -video game - Paananen, Katri (My University, 2020)
Playing and games are one part of the folkloristics studies. Commercial video games are not common research subjects even though they are getting more popular. This multidisciplinary Master’s thesis on the video game, Horizon Zero Dawn, brings up fears we have about our future and which we are mirroring in the game. The themes are revolving around artificial intelligence, climate or climate change and nature. The game presents two different futures, the one before game time and the one after. The future before game time is before and during apocalypse, whereas game time future is post-apocalyptic future. These different futures are defined in this thesis as dystopian and utopian futures, so that they can easily be differentiated from each other. Research material consists about walkthrough YouTube video and Fandom -website, run by the fan base. The research is done based on the storyline, plot and visual setting on of the game, so narrative analysis is used as the research method. Horizon Zero Dawn shows certain fears regarding our future. Dystopian future shows how artificial intelligence and robots destroy the world and climate change is a big issue. Positive aspects of this future are the actions taken against climate change, to counter it. Utopian future shows the world created by the artificial intelligence but one without the problems of climate change. This future does show the future, without bigger fauna, replaced by robots. Fear of artificial intelligence breaks down to smaller things, like being enslaved by the machine, creating killer military robots or next level predators. Horizon Zero Dawn presents many of these fears, if not all of them. Climate change is also presented as problem, in one of the futures. Fears are not the only thing since there is some positive in both futures as well. With artificial intelligence, humankind is able to tackle climate change as well as create a whole new biosphere.
Keywords: video games, folkloristics, folkloresque, climate change, artificial intelligence, dystopian, utopian